Wandering mesenteric cyst - Carlos Ugas-Charcape; Francisco Chincha-Torrejón; Jesús Nivin-Huerta (Elsevier, 2020)
Mesenteric cyst of lymphatic origin are unusual congenital masses that cause abdominal pain, bloating, abdominal mass, nausea. The presentation as a wandering mesenteric cyst is rare reported in general population, and could be confused with ovarian cyst. We present a case of a young female with intermittent abdominal pain and a palpable mass located in pelvis. Presurgical ultrasound (US) identified a large multitabicated cyst in pelvis, which was confirmed by magnetic resonance imaging (MRI). Later, during the physical examination, it was observed that the mass migrated to the upper left quadrant. Histopathological analysis of the resected mass revealed lymphatic origin. To our knowledge, this is the first case reported in Peru. We suggest to be aware of this potential diagnosis of an abdominal wandering cyst and recommend surgical resection as the treatment of choice in these cases.